Implementation of Educational Curriculum Through the Keep Learning Approach to Improve the Quality of Education at SMPN Mesjid Raya: A Literature Study - Suryati Suryati; Rahmattullah Rahmattullah; Siti Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study examines the implementation of the educational curriculum in SMPN Mesjid Raya through the